Fractional order calculus on the estimation of short-circuit impedance of power transformers - Albert, W. Malpica (2019)
This paper reports investigation on the use of fractional order calculus to analytically estimate the inlfuence of skin and proximity effects in the short circuit impedance of power transformers. The aim is to better characterize the medium frequency range behavior of leakage inductances of power transformer models, which include terms to represent the magnetic field diffusion process in the windigns. Comparisons between calculated and measured values are shown and discussed.